Differences in physical properties of coronal bright points and their ALMA counterparts within and outside coronal holes - Matković, Filip; Brajša, R.; Temmer, M.; Heinemann, S. G.; Ludwig, Hans-Günter; Saar, S. H.; Selhorst, C. L.; Skokić, I.; Sudar, D. (Astronomy and astrophysics, 2023)
Aims. This study investigates and compares the physical properties, such as intensity and area, of coronal bright points (CBPs) inside and outside of coronal holes (CHs) using the Atacama Large Millimeter/submillimeter Array (ALMA) and Solar Dynamics Observatory (SDO) observations. Methods. The CBPs were analysed using the single-dish ALMA Band 6 observations, combined with extreme-ultraviolet (EUV) 193 Å filtergrams obtained by the Atmospheric Imaging Assembly (AIA) and magnetograms obtained by the Helioseismic and Magnetic Imager (HMI), both on board SDO. The CH boundaries were extracted from the SDO/AIA images using the Collection of Analysis Tools for Coronal Holes (CATCH) and CBPs were identified in the SDO/AIA, SDO/HMI, and ALMA data. Measurements of brightness and areas in both ALMA and SDO/AIA images were conducted for CBPs within CH boundaries and quiet Sun regions outside CHs. Two equal size CBP samples, one inside and one outside CHs, were randomly chosen and a statistical analysis was conducted. The statistical analysis was repeated 200 times using a bootstrap technique to eliminate the results based on pure coincidence. Results. The boundaries of five selected CHs were extracted using CATCH and their physical properties were obtained. Statistical analysis of the measured physical CBP properties using two different methods resulted in a lower average intensity in the SDO/AIA data, or brightness temperature in the ALMA data, for CBPs within the boundaries of all five CHs. Depending on the CBP sample size, the difference in intensity for the SDO/AIA data, and brightness temperature for the ALMA data, between the CBPs inside and outside CHs ranged from between 2σ and 4.5σ, showing a statistically significant difference between those two CBP groups. We also obtained CBP areas, where CBPs within the CH boundaries showed lower values for the measured areas, with the observed difference between the CBPs inside and outside CHs between 1σ and 2σ for the SDO/AIA data, and up to 3.5σ for the ALMA data, indicating that CBP areas are also significantly different for the two CBP groups. We also found that, in comparison to the SDO/AIA data, the measured CBP properties in the ALMA data show a small brightness temperature difference and a higher area difference between the CBPs within and outside of CHs, possibly because of the modest spatial resolution of the ALMA images. Conclusions. Given the measured properties of the CBPs, we conclude that the CBPs inside CHs tend to be less bright on average, but also smaller in comparison to those outside of CHs. This conclusion might point to the specific physical conditions and properties of the local CH region around a CBP limiting the maximum achievable intensity (temperature) and size of a CBP. The need for the interferometric ALMA data is also emphasised to get more precise physical CBP property measurements at chromospheric heights.